Distribution of Ebony trees (Diospyros spp.) in forests of Shivamogga district, Karnataka, India - Shashwathi, H.S.; Krishnamurthy, Y.L.; Manjunath, K; Jain, Rakshitha H.M. (Indian Forester, 2025)
The Western Ghats of India serve as the primary habitat for numerous valuable flora and fauna species. The Western Ghats in the Shivamogga district of Karnataka state is home to a variety of rare and endemic plant species. A number of tree species categorized under the genus Diospyros L. are commonly referred to as Ebony trees, which hold significant economic value. This particular investigation was focused on conducting a survey of these trees within the forested areas of Shivamogga district, encompassing seven key taluks, with the additional aim of assessing the conservation status of these trees. The survey encompassed a total of 21 locations within the district. The results of the survey revealed the presence of 14 Diospyros species in Shivamogga district, among which one is critically endangered, two are vulnerable, two are least concern, while the rest are either data deficient or have not been evaluated. The highest diversity of Diospyros species was documented in the Agumbe region of Tirthahalli taluk.